Project Level Women’s Empowerment in Fisheries Index (PRO-WEFI) Tanzania data set - Adam, Rahma (2024)
The datasets contain quantitative and qualitative used to assess women’s empowerment using pro-WEFI in in Ilemela and Sengerema districts in Mwanza region of Tanzania